The economic benefits of generation revenue assessment in pool-based market model for restructured electricity supply industry - Ngadiron, Z. (EDP Sciences, 2016)
The electricity supply industry had undergo deregulation and restructuring toward becoming a more transparent and competitive electricity market environment. The pool market model is amongst the most preferred electricity market model. Even though it is a safe option to be more competitive and transparent electricity supply industry, there are issues on the welfare of the generators involved. This paper addresses the pricing issue in the pool market by extending the capacity payment mechanism in the single auction power pool. In the proposed model, the approach of minimum capacity payment involving the efficiency of the generators is introduced. A case study is conducted to illustrate the proposed model. An economic analysis is performed to highlight the merits of the proposed model with the pure pool in term of generation revenue. © 2016 The Authors, published by EDP Sciences.